PENGENALAN PEMROGRAMAN KOMPUTER MENGGUNAKAN HP UNTUK SISWA SMK - Rusdi Sambada; Budi Sugiharto; Lukiyanto Lukiyanto; Yosef Agung Cahyanta; Doddy Purwadianto; PK. Purwadi; Wibowo Kusbandono (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2022)
SMK Pangudi Luhur Leonardo Klaten is children of productive and innovative ages. So it is necessary to get additional knowledge to increase the power of innovation, especially in the face of increasing competition. Computer programming skills can increase creativity. Computer programming can help improve work efficiency, such as repetitive calculations often encountered in the design of machine elements. However, computer programming generally requires a computer or laptop, which is an obstacle for students in learning programming because they generally do not have computer or laptop facilities. In this service activity, the community service team will introduce another alternative to learning programming, namely using a cellphone (HP). Students from the two vocational schools have cellphones, but they have not been used for programming. The students are generally new to using cellphones for communication, social media or games (games). The HP has not been used as a learning tool due to ignorance, the impression that programming is complicated, and not realizing the benefits of programming itself. The service team will introduce programming using cellphones to change the paradigm so that it is hoped that students can develop programming skills independently from this service activity. It is hoped that vocational students will be more creative and develop programming skills according to their work. In addition, the output targets of this service are sending articles to community service journals uploading information on the web and social media.